Structuralism Analysis of the Song Lyrics ‘Ummatī’ by Maher Zain: A Literary Study - Khairawati; Suri; Melinda (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2026)
This study aims to analyze the intrinsic structural elements found in the lyrics of the song Ummatī by Maher Zain based on the structuralism theory proposed by Muzakki. The objective of this research is to identify and explain the intrinsic elements contained in the song lyrics, namely feeling (al-‘āṭifah), imagination (al-khayyāl), idea (al-fikrah), and form (aṣ-ṣūrah). This research employed a descriptive qualitative method with a library research design. The data source was the lyrics of the song Ummatī by Maher Zain. Data were collected through observation and note-taking techniques and were analyzed using an interpretative analysis approach. The results of the study show that the lyrics of Ummatī contain four intrinsic structural elements. A total of 27 data were identified, consisting of 10 data related to feeling (al-‘āṭifah), 9 data related to imagination (al-khayyāl), 1 datum related to idea (al-fikrah), and 7 data related to form (aṣ-ṣūrah). Among these elements, feeling (al-‘āṭifah) was found to be the most dominant element, reflecting the emotional and spiritual messages conveyed through the song lyrics. In conclusion, the lyrics of Ummatī contain interconnected intrinsic structural elements that contribute to the construction of meaning and strengthen the spiritual and moral messages conveyed in the song.